2010
DOI: 10.1111/j.1468-1293.2010.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of the HIV-1 reverse transcriptase M184V mutation using mutation-specific minority assays in a UK surveillance study suggests evidence of unrecognized transmitted drug resistance*

Abstract: The aim of the study was to estimate the levels of transmitted drug resistance (TDR) in HIV-1 using very sensitive assays to detect minority drug-resistant populations. MethodsWe tested unlinked anonymous serum specimens from sexual health clinic attendees, who had not received an HIV diagnosis at the time of sampling, by both standard genotyping and using minority detection assays. ResultsBy standard genotyping, 21 of 165 specimens (12.7%) showed evidence of drug resistance, while, using a combination of stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…It has been demonstrated that newer, more sensitive resistance testing assays in development can now detect mutations down to < 1%. [34][35][36][37][38][39] Therefore, we are potentially missing undetected mutations that may impact response to treatment. Finally, there was wide variability in the time between diagnosis and genotype testing in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that newer, more sensitive resistance testing assays in development can now detect mutations down to < 1%. [34][35][36][37][38][39] Therefore, we are potentially missing undetected mutations that may impact response to treatment. Finally, there was wide variability in the time between diagnosis and genotype testing in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Under selection pressure with 3TC or FTC, both in vitro and in vivo, the M184I mutation usually emerges first and is rapidly replaced by the M184V mutation due to the relative fitness advantage of the latter over the former mutation (13,15,29,48). However, M184I/V mutations are rarely found in cases of transmitted drug resistance (TDR), although the M184V mutation can be detected in newly infected individuals with detection methods that are more sensitive than standard genotyping (12,47,52). As a consequence of low viral fitness, the prevalence of the M184V mutation as a single mutation in newly infected individuals wanes over time (52).…”
Section: Discussionmentioning
confidence: 99%
“…RT enzymes were expressed in Escherichia coli BL21 cells (Invitrogen, Burlington, Ontario, Canada) and purified by nickel affinity chromatography and Q Sepharose ion-exchange chromatography, as described previously (33). The polymerase activity of each recombinant RT preparation was evaluated in triplicate by using the synthetic homopolymeric poly(rA)/p(dT) [12][13][14][15][16][17][18] template/primer (T/P) (Midland Certified Reagent Company) as described previously (41). An active unit of RT was defined as the amount of enzyme that incorporates 1 pmol of dTTP in 10 min at 37°C.…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations